Falewuo (Kebambuan) Glosarium in Society Nias: Ecolinguistic Study - Rahmawati Rahmawati; Dwi Widayati (Randwick International of Education and Linguistics Science Journal, 2021)
Ecolinguistic is a branch linguistics who studies the role of linguistics in problem ecology and environment. Ecolinguistics is an interdisciplinary study that looks at the link between ecosystems and linguistics. This study involves sociology, anthropology, psychology and political science. The socio-ecological aspects greatly affect the balance, preservation and inheritance of the environment for current and future generations. Falewuo's lexicon, for example Niru, still remains in the memory of the older generation, but the entity has become extinct. The purpose of this research is to maintain local ecological wisdoms that need to be included in the discourse of a healthy and green environment (greenspeak), bearing in mind that the soul (ideological, philosophical, socio-ecological concepts) of the community is imbued with these local wisdoms. There are changes due to the emergence of practical tools made of plastic, aluminum and iron. Of course, some that have been used can damage the environment and lose the vocabulary of bamboo in the Nias language because it is rarely used. This study used qualitative methods. The qualitative method is a research method based on existing facts or phenomena that empirically live in the speakers (Sudaryanto, 2015). The theory used is Mbete's ecolinguistic theory. From the research results, it was found that the changes in the lifestyle of the Nias people had changed considerably and did not pay attention to nature as a provider and life. The conclusion of this study is that the pattern of social life has also begun to shift towards individual traits. Environment and language are closely related because every flora and fauna that exists must have the meaning of the wealth of the language-speaking community.